2017
DOI: 10.1159/000477758
|View full text |Cite
|
Sign up to set email alerts
|

First-Line Treatment with Carboplatin plus nab-Paclitaxel and Maintenance Monotherapy with nab-Paclitaxel for a Thymic Carcinoma: A Case Report

Abstract: Thymic carcinomas are rare malignant tumors, located in the anterior mediastinum. For the treatment of these carcinomas, several chemotherapy regimens have been suggested, including carboplatin plus paclitaxel. However, because of the rarity of these tumors, the standard chemotherapy regimen has not yet been established. Here, we report a case of thymic carcinoma that responded to first-line carboplatin plus nanoparticle albumin-bound paclitaxel (nab-paclitaxel) therapy with continuation maintenance nab-paclit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Our retrospective study analyzed the e cacy and safety of combined carboplatin plus nab-paclitaxel therapy in 12 previously untreated patients with advanced thymic carcinoma. While previous case reports have indicated the e cacy of this combination regimen for patients with this disease [15][16][17], no cohort studies have been performed to validate these claims. To the best of our knowledge, ours is the rst study to evaluate the efficacy of combination carboplatin plus nab-paclitaxel in patients with advanced thymic carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Our retrospective study analyzed the e cacy and safety of combined carboplatin plus nab-paclitaxel therapy in 12 previously untreated patients with advanced thymic carcinoma. While previous case reports have indicated the e cacy of this combination regimen for patients with this disease [15][16][17], no cohort studies have been performed to validate these claims. To the best of our knowledge, ours is the rst study to evaluate the efficacy of combination carboplatin plus nab-paclitaxel in patients with advanced thymic carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…These case reports showed that the administration of carboplatin plus nab-paclitaxel resulted in favorable antitumor effects against thymic carcinoma. Funaishi et al (23) reported a case with a PFS time of 10.3 months. Ley et al (24) and Maurer et al (25) suggested the clinical benefit of nab-paclitaxel in recurrent/metastatic gynecological and head and neck carcinomas, which are resistant to paclitaxel and docetaxel.…”
Section: Discussionmentioning
confidence: 99%
“…However, no studies have yet compared the efficacy and safety of PC and nab-PC for advanced thymic carcinoma. A few recent case reports evaluated the efficacy and safety of nab-PC for advanced thymic carcinoma [14][15][16][17][18] . They all demonstrated good responses to nab-PC, with three patients having PFS durations of 9.1, 13, and 10.3 months, respectively.…”
Section: Discussionmentioning
confidence: 99%